Edukasi Strategi Financial Inclusion Dalam Rangka Meningkatkan Kesejahteraan Masyarakat Industri Kawasan Wisata Kabupaten Gresik Jawa Timur - Ratnawati, Tri; Mujanah, Siti; Lokajaya, Nyoman (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2018)
This research aims to produce an educational model of strategy financial inclusion in order to prosper the community, industry, district, gersik, East Java. Basedon the issue of financial inclusion, indicators produced from financial inclusion arebanking, banking products and facilities, banking which is a very important indicator. inimproving the welfare of the industrial community. The education that must be given iscredit management consunier knowledge of credit guidelines over.in debtedness,savings and deposit functions. The strategy, which must be carried out in the short termbased on the attributes found in the research, is to educate financial.inclusion by payingattention to attributes which are significant, providing assistance starting from financialplanning to the preparation of financial statements providing motivation for separatingbetween family finances and business finances of the government is expected to emulatethe role of cooperatives as sitmpau-pinjam institutions not only piniaman saia so loansharks do not play a role.Keywords: Strategy Education, Financial Inclusion, Community Welfare